Insights in Breast Cancer: A Review (Asian Journal of Pharmaceutics (AJP), 2024)
Breast cancer is the most common cancer affecting women in India, with increasing incidence and mortality ratesin recent years. This review addresses the specific challenges associated with breast cancer in the Indian setting,including its epidemiology, risk factors, and disparities in healthcare. In India, the disease tends to be diagnosedat a younger age and at more advanced stages compared to Western populations, primarily due to factors such aslimited awareness, cultural stigma, and restricted access to healthcare services. Delays in diagnosis, socioeconomicchallenges, and the absence of widespread screening programs further complicate the issue. Although recent publichealth initiatives, including awareness campaigns and the establishment of screening and treatment facilities, haveshown progress, significant gaps remain in early detection, individualized treatment, and survivorship care. Thisreview underscores the need for targeted strategies, improved healthcare infrastructure, and equitable access todiagnostic and therapeutic resources to reduce the impact of breast cancer in India and enhance patient outcomes.